Analisis SWOT Dalam Pembelajaran Bahasa Arab Pada Mahasiswa Program Nadwah Usbu’iyyah HMPS PBA - Ramadhan, Fauzan Syahrul (Pedagogical Education and Review of Linguistics, 2025)
This study aims to analyze the factors of strengths, weaknesses, opportunities, and threats (SWOT) in the implementation of the Nadwah Usbu'iyyah program at HMPS PBA, as well as formulate strategies to increase its effectiveness. Using a descriptive qualitative method, this study involved Nadwah Usbu'iyyah participants and HMPS PBA administrators as subjects, with data collection through observation, interviews, and documentation. The results of the SWOT analysis show that this program has the power to improve students' Arabic language skills and provide a useful learning experience. However, there are weaknesses related to flexibility, evaluation, and variety of learning methods. The opportunities that exist include the use of technology, curriculum integration, and competency development. The program also faces threats such as shifting student interest to independent learning and competition with similar programs. This study recommends improvement strategies that focus on flexibility, periodic evaluation, method innovation, and adaptation to digital learning trends.